(untitled) (Gilgameš, 2016)
Among military sketches written by Edmondo De Amicis, That day is notable for its implications in human and literary biography of the budding writer. That day belongs to the group of sketches that were edited in 1867 in the ministerial journal ‹‹L’Italia militare›› and it crossed the following three editions of Military Life in Italy. This persistence betrays the urgency of the treated theme, during the foundation of the national symbolic patrimony: the rout of Custoza on June 24, 1866. In fact, this day compromised the legitimacy of the national Army and the advisability of the military way to Italian unification process, while they were both cornerstones of the cultural politics of the Kingdom of Italy. De Amicis put his sketch through a repeated reworking, because he was torn between being loyal to journalistic deontology of testifying historical truth and being confident of success of the unification process. In the latter attitude it was implicit his link to the ministerial propaganda by ‹‹L’Italia militare›› as well as his debt with the Peruzzi’s salon, the unofficial branch of the Historical Right. Aim of this contribute is to examine the metamorphosis of this war memory along its four stages, by the analysis of the textual variants as well as the linguistic ones. Censures progressively decrease, but even the last stage (1880), separated in time from the battle of Custoza by then, reveals the unsolved emotional split around the event so crucial for the writer’s bildung.